Battery Management System dengan Fitur Adaptive Current Protection Terhadap Suhu - Ade Mahendra Fata; Jefri Lianda; Hikmatul Amri; Adam Adam; Khairudinsyah Khairudinsyah (KOLONI, 2026)
The design and development of a Battery Management System (BMS) with an Adaptive Current Protection feature based on temperature aims to improve battery safety, reliability, and service life by automatically adjusting the charging and discharging current according to temperature conditions. This study employed an experimental method by developing a system consisting of a temperature sensor, current sensor, Battery Management System (BMS) module, ESP32 microcontroller, and an Internet of Things (IoT)-based monitoring platform for real-time data visualization. System testing was conducted under various battery temperature conditions to evaluate its ability to monitor temperature, regulate current adaptively, and transmit measurement data to the monitoring platform. The results showed that the proposed system was able to accurately detect battery temperature changes and automatically adjust the allowable current according to predefined temperature thresholds. Under normal temperature conditions, the system allowed the maximum operating current to maintain battery performance. As the temperature increased, the current limit was gradually reduced, and the protection mechanism was activated when the battery reached unsafe temperature levels. Furthermore, temperature, current, and voltage data were continuously displayed on the IoT monitoring platform, enabling users to monitor battery conditions remotely in real time. The study demonstrates that the proposed Battery Management System with Adaptive Current Protection effectively enhances operational safety, maintains battery performance stability, and contributes to extending battery lifespan.